ANALYSIS OF SHARIAH BANKING PERFORMANCE IN REGIONAL DEVELOPMENT BANKS IN 2022-2023: SHARIA MAQASHID INDEX AND SUSTAINABLE FINANCE PERSPECTIVE - Irsyad Maulana; Muhammad Syukri Albani Nasution; Sugianto (International Journal of Cultural and Social Science, 2025)
This study aims to: (1) assess the performance of Islamic Commercial Banks (BUS) and Sharia Business Units (UUS) within Regional Development Banks (BPD) in Indonesia during 2022–2023 through the lens of the Sharia Maqasid Index (SMI); (2) evaluate their performance from the perspective of Sustainable Finance; and (3) compare the performance of BUS and UUS based on both analytical frameworks. A quantitative-descriptive method was employed, utilizing a document study approach. Data were collected from the annual reports of BUS and UUS at BPDs during the 2022–2023 period and analyzed using SMI indicators and Sustainable Finance principles. A weighted scoring and ranking technique based on Simple Additive Weighting (SAW) was applied to measure performance. The findings reveal that BUS and UUS experienced significant improvement in SMI performance, particularly in the dimensions of education (tahdz?b al-fard) and socio-economic contribution (jalb al-ma?la?ah). Banks such as NTB Syariah and Aceh Syariah excelled in maq??id based financing and zakat distribution, while UUS in Central Java and Nagari demonstrated strength in educational initiatives and social justice. In terms of Sustainable Finance, all banks fulfilled the four key indicators sustainable development, green economy, social responsibility, and separate sustainability reporting. However, most reports remained descriptive and lacked impact-based metrics. Overall, BUS exhibited stronger performance than UUS in integrating both maq??id principles and sustainability practices. These results highlight the need to strengthen performance evaluation frameworks grounded in Sharia values and sustainability to support the transformation of Islamic regional banks into inclusive and impactful institutions.